Efficacy and Safety Analysis of Single‐Port Robotic Assisted Cholecystectomy Using a Novel Surgical Platform: A Bicentre, Single‐Arm, Prospective Phase II Clinical Study - Chao Jing; Kun Liu; Guowei Zhang; Hongwei Wu; Zhe Jia; Guoxin Li; Yaping Zhao; Zhongtao Zhang; Wei Guo (The International Journal of Medical Robotics and Computer Assisted Surgery, 2026)
ABSTRACT Background Single‐port robotic cholecystectomy offers minimally invasive benefits. This trial evaluated the feasibility and safety of a novel system, MicroPort SA‐1000. Methods In this dual centre, single‐arm, prospective study, eligible patients underwent single‐port robot‐assisted cholecystectomy with MicroPort SA‐1000. The primary endpoint was the completion rate, while secondary endpoints included estimated blood loss, operating time, hospital length of stay and complications. Results From June 2023 to December 2023, a total of 44 patients from two centres were enrolled, and all patients underwent single‐port robot‐assisted cholecystectomy without conversion. The median EBL was 10 mL (range 5–200 mL). The total operative time was 88.43 ± 25.87 minutes. The median LOS was 2.5 days (range 1–7 days). No serious surgery‐related adverse events were observed. Conclusions The novel single‐port robot demonstrated feasibility and safety in cholecystectomy with effective triangulation, controlled operative time and reduced trauma. Larger studies are needed to validate its performance across different surgical fields. Trial registration This study was registered at https://www.chictr.org.cn/showproj.html?proj=258677 (ChiCTR2500107401)